CLINICAL-NEUROLOGICAL AND IMMUNOLOGICAL INDICATORS CHILDREN WITH HELMINTHIC INVASION - Khamidova Nargiza Kosimovna (World Scientific Research Journal, 2025)
Summary. A detailed analysis of the main clinical and laboratory parameters in groups of children suffering from allergic rhinitis (AR) with concomitant hymenolepiasis during antiallergic, antiparasitic and complex therapy is given. Patients with AR with hymenolepidoses were divided into three groups: 21 patients received antiallergic therapy, 22 patients received antiparasitic therapy, and 24 patients underwent complex therapy. The maximum clinical effect was achieved by us with the use of complex treatment, which included antiallergic and antiparasitic therapy. The dynamics of immunological parameters after treatment of patients with AR with hymenolepidoses only with antiallergic or antiparasitic drugs shows that, despite the positive result, it is insufficient and does not normalize immunological parameters. Complex antiallergic and antiparasitic treatment has a pronounced immunological effect, activates the severity of the immune response, switches the nature of the immune response to suppressor, and thereby contributes to a faster relief of the allergic process in the body.